Evaluation of the topical spray containing Centella asiatica extract and its efficacy on excision wounds in rats - Sawatdee Somchai; Choochuay Kanuengnit; Chanthorn Wirot; Srichana Teerapol (Acta Pharmaceutica)
Centella asiatica was extracted by methanol. The assay content of triterpenes in the extract was 0.12 % asiatic acid, 0.54 % madecassic acid, 0.25 % asiaticoside and 1.02 % madecassoside. The extract was complexed with hydroxypropyl-β-cyclodextrin (HP-β-CD) and formulated with Eudragit E100, glycerol, PEG 400, copovidone, ethanol and purified water. A clear yellowish solution (F1-F8) was obtained. The formulations had a pH of 5.5–6.0 with viscosity in the range of 20–60 mPa s, surface tension 20.3–24.6 mN m–1 and contact angle less than 20°. The amount of PEG 400 and copovidone affected the film and spreadability. The content of triterpenes in the spray formulation was close to 100 % compared to triterpenes in the extract. The skin irritation study indicated that the formulation was non-irritating in a rat model. An in vivo excision wound healing model showed that wound excision was completely healed after 14 days.